A Qualitative Report of Sport Facilities Management - Wondemagnegn A; Zemikael Getuz (PT. Publikasiku Academic Solution, 2022)
Background: Facility management is the process of planning, administering, coordinating, and evaluating the day-to-day operation of facilities, the technological dimension as applied in sports facility management is used in enhancing the value of facilities and acting as a foundation for smooth operation or processes that define smooth interactions between people and places. Aim: This study aims to assess the state of management of Tirunesh Dibaba and the director of facilities management for the South Youth and Sports Office and facilities and to compare the practices of two different venue facility management positions. Method: This study used qualitative data with in-depth semi-structured interviews with sports facility managers and a purposive sampling approach was used to select sports facility managers. Findings: The results of the study showed that the FM had come a long way to establish itself as a new business opportunity, especially with technological advances, international competition, and tight budget controls every organization wants to concentrate only on core business activities, this gives an opportunity for FM business to grow rapidly. It also requires seasoned professionals with technical and soft skills coupled with the right attitude to make business areas more user-friendly and liked by premise occupants